Alcohol consumption among pregnant women in James Town Community, Accra, Ghana - Joanita Da Pilma Lekettey; Phyllis Dako-Gyeke; Samuel Agyei Agyemang; Moses Aikins (BMC, 2017)
Abstract Background Alcohol consumption among pregnant women is a public health concern, considering its adverse outcomes for both mother and the developing foetus. This study examined factors that facilitate prenatal alcohol consumption, knowledge of adverse outcomes of prenatal alcohol exposure and alcohol expenditure among pregnant women in an urban community in Ghana. Methods In June 2014, a survey was conducted among 250 pregnant women sampled from James Town, an urban community in the Greater Accra Region of Ghana. Data were collected through face-to-face interviews and descriptive statistics conducted. The prevalence of alcohol consumption among women was determined. Pearson chi-square was used to determine associations between variables where necessary. Results Fifty-four percent of the pregnant women were aged 20 - 29 years. Seventy-three percent reported that they have ever consumed an alcoholic beverage before pregnancy. Of these, 77% take alcohol "once a while" and 48% reported taking alcohol during pregnancy. Most of the pregnant women (53%) who currently consume alcoholic beverages had it from friends, and their main reason for prenatal alcohol consumption was socialization (39%). Majority of both current alcohol drinkers (78%) and non-current alcohol drinkers (74%) were aware that prenatal alcohol consumption can lead to spontaneous abortion. Additionally, current alcohol drinkers spend averagely GHS 4.54 (SD 4.63) on their favourite alcoholic drink and overall, also spend averagely GHS 4.63 (SD 4.82) on their entire alcoholic beverage weekly. Over two-thirds (63%) of women reported monthly average income of less than GHS200. Conclusion This study shows high prenatal alcohol consumption in James Town, Accra, despite pregnant women's knowledge of its adverse effects on the developing foetus. Alcohol is usually sourced from friends with socialization noted as a major reason for prenatal alcohol consumption. These results could be used to inform future health advocacies and policies on prenatal alcohol exposure and maternal and child health interventions in the country.